MODERN TRENDS OF ELECTRONIC DEMOCRACY IN RUSSIA - Мельникова, Т. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
Practical examples of implementation the concept of e-democracy in Russia are considered in the article. Conceptual aspects of edemocracy, in particular, reflective government's position regarding the development of this system are disclosed.